Response of Escherichia coli strains carrying plasmid(s) and their plasmidless derivatives to bactericidal activity of human serum and polymorphonuclear leukocytes - Siegfried, L; Puzová, H (Acta microbiologica Hungarica, 1991)
Ten virulence plasmid(s) and antibiotic resistance plasmid(s) carrying Escherichia coli strains isolated from stool of infants with diarrhoea and their plasmidless derivatives were examined for response to bactericidal activity of human serum and intracellular killing of polymorphonuclear leukocytes (PMN). Plasmid(s) carrying isolates exhibited a significantly higher resistance to serum and phagocytosis.
Keywords: virulence; plazmidy; baktericidní aktivita krve; Escherichia coli; Blood Bactericidal Activity; Phagocytosis; Neutrophils; Humans; Plasmids; Virulence; neutrofily; lidé; fagocytóza